Islanding Detection Analysis in Wind Turbine Units Based On Voltage, Frequency and Negative Sequence Components (International Journal of Engineering and Computer Science, 2017)
In this paper a new islanding detection method based on voltage, frequency and negative sequence components are used for the islanding detection analysis in wind turbine units. The proposed method is based on processing of the rate of change of q-axis component of voltage and accelerates of change of frequency and negative sequence component of the voltage and current signals are analyzed through wavelet transform. The proposed techniques are tested on islanding and possible non-islanding condition such as normal operation; sudden load change and tripping of other DG’s etc. The studies reported in this paper are based on time-domain simulations using MATLAB/SIMULINK MODEL.